Extended Abstracts of the 2011 International Conference on Solid State Devices and Materials 2011
DOI: 10.7567/ssdm.2011.j-8-2
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state solution for dark states using a three-level system in coupled quantum dots

Abstract: Quantum dots (QDs) are one of the promising candidates of interconnection between electromagnetic field and electrons in solid-state devices. Dark states appear as a result of coherence between the electromagnetic fields and the discrete energy levels of the system. Here, we theoretically solve the steady-state solutions of the density matrix equations for a thee-level double QD system and investigate the condition of the appearance of a dark state. We also numerically show the appearance of the dark state by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In Ref. 19, we have shown basic results of our experiments. In this study, we have extended the experiments and newly added Figs.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In Ref. 19, we have shown basic results of our experiments. In this study, we have extended the experiments and newly added Figs.…”
Section: Introductionmentioning
confidence: 96%
“…In this study, we experimentally investigated the transport properties of a commercial p-type FinFET, focusing on the noise characteristics in the low-temperature region. 19) The time-dependent noise characteristics were analyzed and compared using a simple simulation. It was demonstrated that the conventional FinFET exhibited a clear Coulomb blockade (CB) and could be treated as a QD in the lowtemperature region.…”
Section: Introductionmentioning
confidence: 99%